Divine pages. Issue 3 (3rd July 2018) - Pettersson, Rune; Strand, Lennart
Abstract: The principle of the Golden Ratio has been used in art and architecture for 2, 500 years to create aesthetic and harmonious proportions. Many handbooks on graphic design recommend it. Since Gutenberg's time, books have often been designed and printed in an upright position that often conforms loosely to the golden ratio. However, this is not true for the Gutenberg Bible. The standard medieval margins were in general more generous than those we have in books today. The common style allowed for more space at the bottom and the outside margins, as compared with today's books. It varies a lot where page numbers are placed in printed books. As it was usually the case in the past, nowadays too are often placed at the bottom of the page.